Field tests of astrometric subsystem. Issue 1 (2nd January 2016) - Zariņš, Ansis; Haritonova, Diāna; Rubans, Augusts; Silabriedis, Gunārs; Zvirgzds, Jānis
Abstract: The paper presents results of astrometric subsystem's functionality tests for space object laser ranging and astrometric position determination device, which is under construction in the Institute of Geodesy and Geoinformatics (GGI) of the University of Latvia. Properties of hardware performance for astrometric image acquisition were evaluated and optimal parameters have been selected. Software for image processing and calculation of instrument orientation was tested and adjustments have been made for real-time operation support. Object tracking properties were evaluated, and mount error model parameters were calculated, using test measurements.